PERANCANGAN APLIKASI MEDIA PEMBELAJARAN UNTUK MELATIH MOTORIK ANAK BERKEBUTUHAN KHUSUS (AUTIS) BERBASIS ANDROID - Dwipa Handayani; Hendarman Lubis (JURNAL REKAYASA INFORMASI, 2019)
Autism is a condition that causes children to only have attention to their own world. Autism is also a category of disability that is characterized by disturbances in social interactions, play patterns, and emotional behavior. Data collection methods used in this study, namely observation, interviews, studies literature, literature studies, questionnaires, and system development methods. System development methods used in the development of learning media applications to train motorized children with special needs based on android is the RAD (Rapid Application Development) method. Functional testing systems are carried out using black box testing. With the development of learning media applications to train motorized children with special needs based on Android, helping parents or therapists in providing learning media for children with special needs (autism) wherever and whenever efficiently. Keywords: application, children with special needs (autism), Rapid Application Development, android.